2000
DOI: 10.1259/bjr.73.871.11089467
|View full text |Cite
|
Sign up to set email alerts
|

Absorbed dose and deterministic effects to patients from interventional neuroradiology.

Abstract: Following the presentation of radiation-induced skin effects by three patients who had undergone glue embolisation of intracranial arteriovenous malformation (AVM), measurements were made of absorbed dose to the skin of patients undergoing other interventional neuroradiological procedures that involve long fluoroscopy times. The maximum absorbed dose to the skin measured by thermoluminescent dosemeters during these procedures was 4 Gy. From these measurements and from records of fluoroscopy time and the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 6 publications
2
48
0
6
Order By: Relevance
“…This recognized radiation risk has prompted multiple medical committees to regulate and monitor equipment and recommend techniques to reduce the exposure. [1][2][3] While studies have identified cerebral embolization as a high-radiation exposure procedure, [4][5][6][7][8][9][10][11]19 the cumulative exposure to the patient from repetitive procedures and imaging studies within a single hospitalization has not been documented. We demonstrate that the radiation exposure of the index procedure substantially underestimates the total radiation given through a full hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This recognized radiation risk has prompted multiple medical committees to regulate and monitor equipment and recommend techniques to reduce the exposure. [1][2][3] While studies have identified cerebral embolization as a high-radiation exposure procedure, [4][5][6][7][8][9][10][11]19 the cumulative exposure to the patient from repetitive procedures and imaging studies within a single hospitalization has not been documented. We demonstrate that the radiation exposure of the index procedure substantially underestimates the total radiation given through a full hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term outcome studies have not explored the effects of radiation in the patient with subarachnoid hemorrhage, and reports of short-term complications of radiation exposure are limited. 6,[21][22][23] Because the essential question that underlies this and other studies of radiation exposure for this patient group is one of short-and long-term risk, better controlled longitudinal studies are needed to follow patients for the development of skin, lens, thyroid, and cerebral injury or neoplasia.…”
Section: Risk Of Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Patients at risk should be counselled and advised to check for skin changes 2-4 weeks after the procedure. Several papers present data on measured absorbed dose to patient skin following interventional neuroradiology [23][24][25][26] or energy imparted to the patient [27] in order to correlate with acute and late radiation effects respectively. In this paper, we report on measured local skin doses on the head of patients undergoing diagnostic or therapeutic neuroangiography using thermoluminescence dosimeters, TLD, and compare these with the doses at the IRP as estimated by the x-ray unit in order to provide a method to determine the risk of local overexposure of skin and eye-lenses.…”
Section: Introductionmentioning
confidence: 99%
“…The numbers of lengthy complex interventions such as embolizations, percutaneous porto-systemic shunt placements, invasive electrophysiology, and catheter ablations have continuously grown over the last years. With some of these procedures deterministic radiation effects such as erythema or loss of hair have been reported (84,85). These damages are-regardless of patient age, morbidity, or life expectancy-intolerable and must be avoided by all means.…”
Section: Safety Aspectsmentioning
confidence: 99%